1997
DOI: 10.1023/a:1005868105651
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The expression of genes encoding conglutin gamma and a leginsulin-like protein has been examined in narrow-leafed lupin, Lupinus angustifolius L. Conglutin gamma is a homologue of basic 7S globulin (Bg), the insulin and leginsulin binding protein from soybean. Accumulation of conglutin gamma mRNA, as assessed by northern assays and reverse-transcription PCR, was tightly regulated both spatially and temporally in lupin plants and was detected almost exclusively in developing seeds. Similar tissue and temporal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Sophora japonica , the Japanese pagoda tree) harbors the more divergent albumin I known to date. Consensus legume phylogeny therefore dates the A1b family back to the ancestor of S. japonicum and all other known families harbouring such peptides, especially the genistoid clade –genus Lupinus ; Uniprot Q96474 [ 46 ], with an estimated 56–58.5 My/late paleocene origin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sophora japonica , the Japanese pagoda tree) harbors the more divergent albumin I known to date. Consensus legume phylogeny therefore dates the A1b family back to the ancestor of S. japonicum and all other known families harbouring such peptides, especially the genistoid clade –genus Lupinus ; Uniprot Q96474 [ 46 ], with an estimated 56–58.5 My/late paleocene origin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the draft assembly is still valuable in studying the functional genes in lupin. For example, previous studies on lupin storage proteins were based upon gene expression (including mRNA and cDNA translations) [50], gene product (protein) isolation [51], or homology with storage proteins from other species [52]. In this study, we identified the scaffold sequences for each of the lupin storage proteins, which, for the first time, provided the genomic DNA sequences flanking the protein genes.…”
Section: Discussionmentioning
confidence: 99%
“…There is little, or no, transcription of these genes in early development but then transcription progressively increases to reach its highest level midway through development (20 to 22 days after flowering), followed by a sharp decline [4,38]. In the genome of another legume, the narrow-leafed lupin ( Lupinus angustifolius ), a PA1b-like gene was detected that showed, within the same region, 96% sequence identity with the leginsulin gene from soybeans [39]. The gene was functional at the transcriptional level since the corresponding mRNAs were detected but they were in very low quantities and, almost exclusively, in developing seeds (mainly in cotyledons 40 days after anthesis) [39].…”
Section: Pa1b Biodiversitymentioning
confidence: 99%
“…In the genome of another legume, the narrow-leafed lupin ( Lupinus angustifolius ), a PA1b-like gene was detected that showed, within the same region, 96% sequence identity with the leginsulin gene from soybeans [39]. The gene was functional at the transcriptional level since the corresponding mRNAs were detected but they were in very low quantities and, almost exclusively, in developing seeds (mainly in cotyledons 40 days after anthesis) [39]. However, unlike in soybeans [29], no evidence was found for the expression of the leginsulin-like gene in the radicle of lupins (two days after germination), suggesting a tight temporal regulation of the gene in developing and germinating seeds [39].…”
Section: Pa1b Biodiversitymentioning
confidence: 99%